2024
DOI: 10.5114/jhk/185524
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and Metabolic Responses during Repeated Sets of Bench Press Exercise to Exhaustion at Different Ranges of Motion

Athanasios Tsoukos,
Michał Krzysztofik,
Michal Wilk
et al.

Abstract: This study compared the acute effects of different ranges of motion (ROM) on fatigue and metabolic responses during repeated sets of bench press exercise. Ten resistance trained men performed three sets to momentary failure with two-min rest intervals at three different ROM: full ROM (FULL), and partial ROM in which the barbell was moved either at the bottom half (BOTTOM) or the top half (TOP) of the full barbell vertical displacement. In TOP, a higher load was lifted, and a higher total number of repetitions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 65 publications
4
5
3
Order By: Relevance
“…A previous study showed differences in applied force between different ROMs in the bench press exercise, but this was in isometric muscle actions (Murphy et al, 1996). Those authors found that maximal isometric force was almost 30% higher at an elbow angle of 120 ⁰ which is close to the starting angles in the present study (TOP: 114 ± 4 ⁰ ) compared to an angle of 90 ⁰ (Murphy et al, 1996) which is also close to the starting angles of the FULL and BOTTOM ROMs in the present study (BOTTOM: 77 ± 9 ⁰ and FULL: 78 ± 12 ⁰ ) (Tsoukos et al, 2024). Interestingly, the percentage difference in force among TOP, FULL and BOTTOM ROM in that study were similar to the values reported in the present study (Murphy et al, 1996).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…A previous study showed differences in applied force between different ROMs in the bench press exercise, but this was in isometric muscle actions (Murphy et al, 1996). Those authors found that maximal isometric force was almost 30% higher at an elbow angle of 120 ⁰ which is close to the starting angles in the present study (TOP: 114 ± 4 ⁰ ) compared to an angle of 90 ⁰ (Murphy et al, 1996) which is also close to the starting angles of the FULL and BOTTOM ROMs in the present study (BOTTOM: 77 ± 9 ⁰ and FULL: 78 ± 12 ⁰ ) (Tsoukos et al, 2024). Interestingly, the percentage difference in force among TOP, FULL and BOTTOM ROM in that study were similar to the values reported in the present study (Murphy et al, 1996).…”
Section: Discussionsupporting
confidence: 87%
“…Also, impulse was higher in TOP compared to FULL and BOTTOM ROMs. Impulse is the integral of force with respect to time and, as force and time under tension were significantly higher in TOP compared to FULL and BOTTOM, it is reasonable for impulse to be significantly higher in TOP compared to FULL and BOTTOM ROMs (Tsoukos et al, 2024). Thus, it may be suggested that the TOP ROM may be used to increase absolute loading in the bench press exercise and help athletes in sports where the absolute maximum force of elbow extensors is essential, i.e., individuals whose sports involve Journal of Human Kinetics, volume 91, March 2024 http://www.johk.pl forceful pushing or throwing actions, such as the shot put or boxing (Lopez-Laval et al, 2020;Terzis et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations